[The Consumer does Benefit from Feasible Price Stability]: Rejoinder - Samuelson, Paul A. (Quarterly Journal of Economics, 1972)
Rejoinder Get access Paul A. Samuelson Paul A. Samuelson Massachusetts Institute of Technology Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 86, Issue 3, August 1972, Pages 500–503, https://doi.org/10.2307/1880808 Published: 01 August 1972